Prognostic significance of free peritoneal tumor cells in the peritoneal cavity before and after neoadjuvant chemotherapy in patients with gastric carcinoma undergoing potentially curative resection - Lorenzen, Sylvie; Panzram, Benjamin; Rosenberg, Robert; Nekarda, Hjalmar; Becker, Karin; Schenk, Ulrich; Höfler, Heinz; Siewert, Jörg R.; Jäger, Dirk; Ott, Katja (Annals of surgical oncology, 2010)
Free peritoneal tumor cells (FPTCs) are an independent prognostic factor in patients undergoing curative resection for gastric carcinoma. Whether neoadjuvant chemotherapy (NAC) can eliminate FPTCs in the peritoneal lavage remains unclear. The aim of the study was to determine the effect of NAC on FPTCs.